DG Sanginga, DRC Presidential envoy visit Chief Obasanjo’s Presidential library - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Following the need to develop a plan to transform agriculture in DRC, H.E President Tshisekedi sent a special envoy to IITA Headquarters - Mr. Pacifique Kahasha Birindwa, accompanied by Mr. Felix Karume Ntwali. Mr Birindwa said the president is aware of IITA’s transformational work in Nigerian agriculture and will like to do the same for DRC.